Measurement of Texture Gradient in Heavily Cold‐Drawn Pearlitic Wires. Issue 4 (6th September 2017) - Jamoneau, Aurélie; Schmitt, Jean‐Hubert; Solas, Denis
Abstract : It is well established that cold‐drawing of pearlitic wire develops a strong anisotropy due to a preferential <110> orientation of the ferrite phase parallel to the wire axis. The subsequent wire behavior during torsion, which mainly occurs during assembling of drawn wires, is correlated with the texture and its gradient along the wire radius. Although different attempts were made in the past to measure the texture after drawing, it is still challenging since the final wire diameter is on the order of 0.3 mm. The paper presents a simple and robust method to measure the texture gradient by X‐ray diffraction. First, to overcome the problems of a composite sample made of parallel wires, an isotropic reference sample is prepared by cycles of austenite transformation and quenching. The texture gradient is measured at different thicknesses by dissolving the external surface of the wires. This allows the investigation of the first 40 μm of depth. Finally, the results are compared with EBSD measurements on a longitudinal cross‐section to quantify the influence of the drawing conditions: A flat schedule with constant die angles favors a <110> fiber texture with a weak gradient, while increasing the drawing angle for three dies increases the gradient. Abstract : An isotropic pearlitic wire is used as a reference with which to correct pole figures obtained by X‐ray diffraction on drawn wire surface (R). The textural evolution is measured along the radius via successive surface dissolutions (0.87R and 0.73R). Results are compared to EBSD maps at equivalent depths to quantify the effects of drawing conditions.